The GSSP Method of Chronostratigraphy: A Critical Review - Lucas, Spencer G. (Frontiers in Earth Science, 2018)
The use of boundary stratotypes to define chronostratigraphic units began in the 1960s, and, in the 1980s, these were called Global Stratotype Sections and Points (GSSPs). Approximately two-thirds of the GSSPs of the bases of the Phanerozoic stage (71 of 102 in September 2018) have been ratified by the International Commission on Stratigraphy. However, this apparent progress toward precise definition of a Phanerozoic chronostratigraphic timescale is underlain by multiple problems of philosophy and methodology that include: (1) inconsistency in how chronostratigraphic units are being named and defined; (2) arbitrary decisions as to GSSP level, many based on arbitrarily chosen points in hypothetical chronomorphoclines of microfossils; (3) hierarchical reductionism, which makes the stage base the same as the base of the series, system, erathem and eonothem, thereby trivializing the significance of the boundaries of these larger chronostratigraphic units; (4) stability achieved by the non-scientific process of designating a GSSP once ratified as immutable; (5) the unworkable concept of a standard set of global stages; (6) the fallacy that a GSSP location can somehow define a recognizable (correlateable) global time line; (7) imprecision in GSSP correlation because the primary signals are largely single taxon biotic events that are inherently diachronous due to the limitations of fossil distributions by sampling, facies and provincialism; and (8) the politics of the International Commission on Stratigraphy and the small groups of specialists who select and vote on GSSPs. Chronostratigraphy needs to return to the concepts of natural chronostratigraphy, with improvements based on modern techniques like quantitative biostratigraphy. We need to standardize the chronostratigraphic scale, and the International Commisssion on Stratigraphy needs to rethink the philosophy and practices by which this is being done, so that we can move forward to produce the most informative chronostratigraphy possible based on a consistent methodology and sound science. .